Rosa Navarro-Haydon: Struggling for Locally Relevant Science Education in Puerto Rico. 1926-1966 - Gonzalez-Espada, Wilson Javier (2019)
Rosa Navarro-Haydon played a fundamental role during a critical turning point in the history of science education in Puerto Rico. This eminent scholar developed and implemented elementary-level science curricula for public schools, wrote and published science booklets, articles and textbooks and trained thousands of science teachers. Rosa Navarro-Haydon was one of the first scholars to engage in science communication activities in Puerto Rico, such as writing science magazine articles for the general public. Unfortunately, education and scientific communities are unaware of the countless professional contributions made by Rosa Navarro-Haydon and her life as a science educator pioneer in Puerto Rico.